The Drivers of Non-Revenue Water : How Effective are Non-Revenue Water Reduction Programs? - van den Berg, Caroline (World Bank Group, Washington, DC, 2014)
To many, reducing water losses is seen as key to more sustainable water management. The arguments to reduce water losses are compelling, but reducing water losses has turned out to be challenging. This paper applies a panel data analysis with fixed effects to determine the major drivers of non-revenue water, which is define as the volume of water losses per kilometer of network per day. The analysis uses data from the International Benchmarking Network for Water and Sanitation Utilities, covering utilities in 68 countries between 2006 and 2011. The analysis finds that non-revenue water is driven by many factors. Some of the most important drivers are beyond the control of the utility, such as population density per kilometer of network, the type of distribution network, and the length of the network, which are largely the result of urbanization and settlement patterns in the localities that the utility serves. The opportunity costs of water losses are also key in explaining what drives non-revenue water. The paper finds that very low opportunity costs of water losses have an adverse effect on the reduction of non-revenue water. Country fixed effects turn out to be important, meaning that the environment in which the utility operates has an important impact on non-revenue water levels. An important conclusion is that the design of non-revenue water reduction programs should study the main drivers of non-revenue water to provide utility managers with a better understanding of what can be achieved in terms of non-revenue water reduction and whether the benefits of these reductions exceed their costs.